Lecturers' Beliefs and Classroom Practices in Promoting Students' Critical Thinking Skills in Language Research Class - Trisnanto, Dimas Adika; Fitriati, Sri Wuli; Wulandari, Rini Susanti (Universitas Muhammadiyah Yogyakarta, 2000)
Background: Developing students' critical thinking skills has become an essential goal that needs to be realized in the scope of EFL education learning. Still, the application of learning practices often experiences various challenges. Thus, this study explored how English language education lecturers' beliefs and their classroom practices in promoting students' critical thinking skills in Language Research classrooms. Objective: The study aimed to examine English language lecturers' beliefs and how they are represented in their teaching practices. Methods: This study used a qualitative case study research design involving English language education study program lecturers in the Language Research class. Data was obtained through various sources, including interviews, classroom observations and document analysis. Data was analyzed using thematic analysis, referring to Braun and Clarke's (2006) six analysis steps. Findings: Lecturers believed positively in the importance of critical thinking skills, grounded in their educational background and teaching philosophy. In teaching practice, they used strategies including dialogic and Socratic questions, real-world case studies, inquiry-based approaches, collaborative learning and feedback. Conclusion: This study concludes that although lecturers are relatively high agencies in the context of critical thinking promotion, there is a need that institutional and contextual support to maintain congruence between beliefs and practice. Further studies can explore the viewpoint of students and the effects of institutional arrangements on teaching critical thinking skills.